Leadership lessons from the Cherokee Nation : learn from all I observe - Smith, Chadwick Corntassel (McGraw-Hill Education, 2013)
Offering a holistic approach to the subject; this book combines Cherokee wisdom handed down from generation to generation with a smart leadership approach to explain how to become a powerful leader inside and direct your energy outward to accomplish any goal you set your mind to. --